Perception of young adult towards tiktok and douyin application - Du, Miao (2023)
The study is conducted to determine the perception of young people towards the applicationsTikTok and DouYin. This study also aims to investigate the different feedback and psychology of young people towards the difference between TikTok and DouYin, andtodetermine the various impacts of TikTok and Douyin on young people's decision to use short video apps. In this study, quantitative research via a questionnaire to collect primary datasuchas population profile, frequency and intensity of use, and reasons for use. The Use andGratification were used as a theoretical framework to examine the interaction and evolutionbetween DouYin and TikTok. Descriptive analysis, cluster population analysis, and significant difference analysis were used to explore the different characteristics, habits, attitudes, satisfaction, needs, and usage patterns of the two applications. Summarize the specific differences between the two applications and conduct a comprehensive studyandanalysis to reveal the different evaluations of TikTok and DouYin among young people. Theresults of this study show that DouYin's app design and content are more attractive thanTikTok's, and that younger groups are more inclined to use Douyin for browsing or posting, although Douyin is limited to the Chinese market. The study concludes that the content, appdesign, duration, music, and limitations of short video apps will influence young people's choices. To occupy the local market, the short videos of foreign brands need to use a relatively large number of channels to optimize communication opportunities and integratelocal culture to arouse empathy and resonance for Chinese culture among foreign users, especially among certain age groups with high satisfaction, which need to increase the stickiness of users. This research is also relevant to the expansion of other short videoappsinthe overseas market.